2018
DOI: 10.1111/andr.12506
|View full text |Cite
|
Sign up to set email alerts
|

The CATCH checklist to investigate adult‐onset hypogonadism

Abstract: Adult-onset hypogonadism is a syndrome often underdiagnosed, undertreated, or incompletely explored. There are various reasons for this: firstly, undefined age range of men in whom testosterone levels should be investigated and then no definitive serum cutoff point for the diagnosis of hypogonadism; and finally, variable and non-specific signs and symptoms; men and physicians do not pay adequate attention to sexual health. All these factors make the diagnostic criteria for hypogonadism controversial. The evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 166 publications
(252 reference statements)
7
31
0
Order By: Relevance
“…15,16 A recent study suggested that the early diagnosis of both hypogonadism and related comorbidities may be helpful for the patients in terms of changing lifestyle and appropriate treatment. 17 Despite existing strong evidence demonstrating the role of testosterone as a protective hormone on the kidney function in men, there are controversies on the influence of decreased levels of endogenous testosterone on developing CKD in men. 4,7,18 This long term follow-up study aimed to investigate the incidence and hazard ratio of CKD among male adults with low concentrations of testosterone compared to controls with normal concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 A recent study suggested that the early diagnosis of both hypogonadism and related comorbidities may be helpful for the patients in terms of changing lifestyle and appropriate treatment. 17 Despite existing strong evidence demonstrating the role of testosterone as a protective hormone on the kidney function in men, there are controversies on the influence of decreased levels of endogenous testosterone on developing CKD in men. 4,7,18 This long term follow-up study aimed to investigate the incidence and hazard ratio of CKD among male adults with low concentrations of testosterone compared to controls with normal concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Given the hypogonadism is widely defined as TT < 12 nmol/L . We therefore compared the difference in SDBG between the low‐and high‐ TT groups divided by TT = 12 nmol/L (low TT group 1.81 ± 0.07, and high TT group 2.13 ± 0.09, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size of older patients was small (a total of 72 patients aged >60 years), which may have led to unobserved statistical differences in hypoglyc a emia between the groups with different levels of TT. Moreover, considering the sample size was moderate, so we included patients without age criteria, though the testosterone is more affected after 40 years . Second, this cross‐sectional study could not clearly indicate the causality between testosterone levels and glyc a emic variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the prevalence of low TT among firefighters has not been investigated, despite several population studies that have demonstrated an association between low testosterone and dysmetabolic conditions, 20 and a high prevalence of obesity, diabetes, and metabolic syndrome in the fire service, which in turn are associated with increased risk of cardiovascular events 1,21‐23 . Thus, we initially sought to determine the prevalence of low testosterone among firefighters, considering their high rates of obesity.…”
Section: Introductionmentioning
confidence: 99%